The Body as Evidence for the Nature of Language - Sandler, Wendy (Frontiers in Psychology, 2018)
Taking its cue from sign languages, this paper pulls together a range of studies to support the proposal that the recruitment and composition of body actions counts as evidence for linguistic properties. Adopting the view that compositionality is the foundational organizing property of language, we find first that actions of the hands, face, head, and torso in sign languages directly reflect linguistic components, as well as certain aspects of compositional organization among them that are common to all languages, signed and spoken. Work on emerging sign languages strengthens the approach by showing that the gradual recruitment of bodily articulators for linguistic functions directly maps the way in which a new language increases in complexity over time. While compositional communication is almost exclusively restricted to humans, it is not restricted to language. In the spontaneous, intense emotional displays of athletes, different emotional states are correlated with actions of particular face and body features and feature groupings, indicating a much more ancient compositional foundation for language.